Benjamin Titus Roberts family papers - Roberts, Benjamin Titus, 1823-1893.; Roberts, Anna A. Rice, -1881.; Roberts, Benson Howard; Roberts, Ellen Lois Stowe; Roberts, Emma Sellew; Roberts, George Lane.
Family and general correspondence, diaries, notebooks, speeches and writings, and other papers of Benjamin Titus Roberts and members of his family: his wife, Ellen Lois Stowe Roberts, his sons, lawyer George Lane Roberts and clergyman Benson Howard Roberts, and their wives, Anna A. Rice Roberts and Emma Sellew Roberts, respectively. Topics include family and domestic matters; Benjamin Titus Roberts's work and association with the Free Methodist Church of North America, especially in upstate New York; Benson Howard Roberts's duties as principal of the Chili Seminary, later A. M. Chesbrough Seminary, North Chili, N.Y.; George Lane Roberts's law practice and business ventures in Bradford, Pa., and Rochester, N.Y., and brief residency in South America; and matters relating to the allied Rice, Sellew, and Stowe families. Includes material on the dissension and division within the Genesee Annual Conference of the Methodist Episcopal Church in the 1850s and the overseas missionary work of the Free Methodist Church in the 1880s and 1890s.
Microfilm edition of the portion of the collection processed before 1990 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Clergyman and founder of the Free Methodist Church of North America.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Rice family; Roberts family; Sellew family; Stowe family; A.M. Chesbrough Seminary (North Chili, N.Y.); Chili Seminary (North Chili, N.Y.); Free Methodist Church of North America; Methodist Episcopal Church. -- Genesee Annual Conference; Methodist Church -- Clergy; Methodist Church -- Missions; Methodist Church -- New York (State); Methodist theological seminaries -- New York (State) -- North Chili; Practice of law -- New York (State) -- Rochester; Practice of law -- Pennsylvania -- Bradford; Bradford (Pa.) -- Commerce; Rochester (N.Y.) -- Commerce; South America -- Description and travel; Clergy